A Phenomenological Study of Teacher Experience during Implementation and Initial Sustainability of the National Math and Science Reform Initiative of a Middle Georgia High School - Thompson, Ike Charles (My University, 2019)
The focus of this dissertation was to study the experiences and perceptions of four teachers involved in the implementation and the sustaining of the National Math and Science Initiative. The National Math and Science Initiative (NMSI) is a program funded by the private sector, with some financial backing from various divisions of the federal government. This reform was developed, in part, to respond to the United States of America’s STEM (Science, Technology, Engineering, and Mathematics) crisis in the U.S. (National Math and Science Initiative, 2013). The National Math and Science Initiative (NMSI) is an aggressive reform that serves to raise interest in these areas by providing schools with resources, training, and methods for restructuring. The goal is to put more students, especially those of underrepresented populations, in Advanced Placement classrooms. The NMSI reform provides guidance, financial support, and training for teachers and students for three years. This phenomenological study focused on the experiences of four teachers responsible for implementing the reform. The purpose of this study was to investigate 1) the experiences teachers had in implementing the NMSI reform, 2) what factors contributed to implementation, and 3) to what degree the reform was sustained after the initial three-year onboarding. Themes, implications for future research, and recommendations are presented. The findings in this study address the impact the National Math and Science Initiative can have on the teaching and learning climate of an institution and may serve as a foundation for future studies.
CHAPTER I: INTRODUCTION 1 -- Statement of the Problem 11 -- Conceptual Framework 13 -- Constructivism 13 -- Motivation Theory 15 -- Change Theory 19 -- Purpose of Study 23 -- Research Questions 26 -- Site Description and Significance 26 -- Middle Georgia County High 30 -- Procedures 32 -- Limitations 37 -- CHAPTER II: REVIEW OF LITERATURE 40 -- Reform Implementation 42 -- Teacher Professional Learning 46 -- Reform Sustainability 48 -- Teacher Performance Pay 52 -- National Math and Science Initiative 58 -- CHAPTER III: RESEARCH METHODS 67 -- Phenomenology 68 -- Units of Analysis 75 -- Research Site and Gaining Access 77 -- Sampling 79 -- Data Collection 81 -- Observation 82 -- Interviewing 86 -- Data Analysis 91 -- Validity 97 -- Reliability 101 -- Subjectivity 101 -- Ethical Concerns 104 -- Summary 106 -- CHAPTER IV: FINDINGS 107 -- Introduction 111 -- Participant Profiles 107 -- Participant 1: Ashley Lynn 111 -- Participant 2: Labrock 131 -- Participant 3: Rache l 140 -- Participant 4: Lauren 153 -- Emergent Themes 164 -- Shared Participants Profile 164 -- CHAPTER V: DISCUSSION 177 -- Introduction 177 -- Research Question 1 177 -- Research Question 2 178 -- Research Question 3 178 -- Discussion 178 -- Theme 1 179 -- Theme 2 185 -- Theme 3 190 -- Theme 4 194 -- Theme 5 198 -- Theme 6 202 -- Theme 7 207 -- Financial Incentives 207 -- Time on task 208 -- Collaborative Planning and PL 210 -- Resources 212 -- Open Enrollment 215 -- Perception of the AP student 217 -- Expectation of the AP teacher 218 -- Implications for Practice 219 -- Future Research 222 -- Performance Pay 222 -- Sustainability 223 -- Perception of non-AP teachers 224 -- Conclusion 225 -- REFERENCES 228 -- APPENDICES 240 -- APPENDIX A: Study Permissions 240 -- APPENDIX B: Observation Instrument 245 -- APPENDIX C: Semi-structured Interview Instrument 248 -- APPENDIX D: Flow Chart 256 -- APPENDIX E: Coding and Significance Chart 258.
Keywords: Dissertations, Academic--United States; Education; Educational change; Master teachers; Merit pay; National Math and Science Initiative (NMSI)